Optimal design of light microclimate and planting strategy for Chinese solar greenhouses using 3D light environment simulations - Xu, Demin; Henke, Michael; Li, Yiming; Zhang, Yue; Liu, Anhua; Liu, Xingan; Li, Tianlai (Energy (Oxford), 2024)
Light has a significant impact on crop production. The objective of this study was to explore the optimal lighting structure parameters and the corresponding planting strategy of Chinese solar greenhouses (CSG). Taking CSG-grown melons as the experimental subject, we have developed a detailed 3D model capable of calculating the light interception at a single organ level, e.g., for individual leaves. The quantitative research was carried out after verifying the proposed model using field data. The results indicated that the reasonable ridge height for the most common 9 m span CSG was 4.9 m, and the horizontal projection on rear roof was 1.6 m in Shenyang area. In comparison with the experimental greenhouse, the optimized greenhouse improved crop light interception by 0.5 % and increased the average air temperature by 9.3 % during winter. The suitable planting strategy was E-W row orientation, with a ridge spacing of 1.2 m, a row spacing of 0.4 m, and a plant spacing of 0.38 m. Compared with the N–S row orientation, the crop light interception increased by 7.1 % and 10.8 % in the two growing seasons, respectively. The model described herein can serve as a foundation for the production of CSG. •The optimal lighting structure of CSG was determined through model analysis.•The average air temperature of the optimized greenhouse was increased by 1.37 °C.•A calculation model for light interception of individual melon leaf was established.•The feasibility of E-W row planting configuration within greenhouse were clarified.